2005
DOI: 10.1111/j.1462-2920.2005.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Response and adaptation of different methanotrophic bacteria to low methane mixing ratios

Abstract: Described genera of methanotrophic bacteria are present in most upland soils, but it is not known whether these are sufficiently oligotrophic to oxidize methane at its trace atmospheric mixing ratio of 1.75 ppmv. Members of the genera Methylocystis, Methylosinus, Methylocaldum and Methylobacter were isolated from different upland soils and compared with type strains for growth and activity under low methane mixing ratios. The specific affinity (a0s) varied by about one order of magnitude among different methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
157
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 47 publications
(82 reference statements)
12
157
2
2
Order By: Relevance
“…Physiological characterizations of isolated methanotrophs (types I and II) have shown that the growth of type I methanotrophs is greater than that of type II methanotrophs at higher methane concentrations, whereas type II methanotrophs outgrow type I under relatively low methane concentrations. [45][46][47] Taken together with previous observations, our findings strongly suggest that the rate of methane emission, linked to vegetation type, is a decisive factor determining the predominance of particular methanotrophs in a wetland.…”
Section: Populations Of Aerobic Methanotrophic Bacteriasupporting
confidence: 60%
“…Physiological characterizations of isolated methanotrophs (types I and II) have shown that the growth of type I methanotrophs is greater than that of type II methanotrophs at higher methane concentrations, whereas type II methanotrophs outgrow type I under relatively low methane concentrations. [45][46][47] Taken together with previous observations, our findings strongly suggest that the rate of methane emission, linked to vegetation type, is a decisive factor determining the predominance of particular methanotrophs in a wetland.…”
Section: Populations Of Aerobic Methanotrophic Bacteriasupporting
confidence: 60%
“…The a s 0 values of pMMO2 determined for wild-type strain SC2 and mutant SC2-P2 (Table 4) were higher than those measured for cultured methanotrophs recently tested for their response to low methane mixing ratios (7). Of the strains studied in ref.…”
Section: Resultsmentioning
confidence: 98%
“…7. In brief, the serum vials were connected to a 54-liter gas reservoir (2 ϫ 27-liter plastigas bags, Linde) via tygon and iso-versinic tubes.…”
Section: Growth Experiments Under Low Methane Mixing Ratiosmentioning
confidence: 99%
“…This is much higher than the atmospheric methane concentration (1.8 ppm v , corresponding to 2.3 nM), but cultures of and sequences affiliated to Methylosarcina have so far only been retrieved from high-methane environments, such as lake sediments, rice paddies and landfills (Wise et al, 2001;Kalyuzhnaya et al, 2005;Henneberger et al, 2011;. Apparent K m constants in environments with high source strength are usually 41 mM CH 4 (Conrad, 1996), but some cultivated MOB, in particular Methylocystis strains, may grow for an extended period at 120 nM CH 4 and less (Knief and Dunfield, 2005). For Methylosarcina-like MOB, however, activity at low methane concentrations has not yet been reported.…”
Section: Microarray Analysesmentioning
confidence: 99%